Marker-less tracking system for multiple mice using Mask R-CNN - Sakamoto, Naoaki; Kakeno, Hitoshi; Ozaki, Noriko; Miyazaki, Yusuke; Kobayashi, Koji; Murata, Takahisa (Frontiers in Behavioral Neuroscience, 2023)
Although the appropriate evaluation of mouse behavior is crucial in pharmacological research, most current methods focus on single mouse behavior under light conditions, owing to the limitations of human observation and experimental tools. In this study, we aimed to develop a novel marker-less tracking method for multiple mice with top-view videos using deep-learning-based techniques. The following stepwise method was introduced: (i) detection of mouse contours, (ii) assignment of IDs to each mouse, and (iii) correction of mis-predictions. The behavior of C57BL/6 mice was recorded in an open-field arena, and the mouse contours were manually annotated for hundreds of frame images. Then, we trained the mask regional convolutional neural network (Mask R-CNN) with all annotated images. The mouse contours predicted by the trained model in each frame were assigned to IDs by calculating the similarities of every mouse pair between frames. After assigning IDs, correction steps were applied semi-automatically to remove the predictive errors. The established method could accurately predict two to four mice for first-look videos recorded under light conditions. The method could also be applied to videos recorded under dark conditions, extending our ability to accurately observe and analyze the sociality of nocturnal mice. This technology would enable a new approach to understand mouse sociality and advance the pharmacological research.